Pengaruh Kejelasan Sasaran Anggaran, Komitmen Organisasi dan Ketidakpastian Lingkungan Pada Ketepatan Anggaran (Studi Empiris di SKPD Pemerintah Provinsi Bali) - Kusuma, Eka Arya; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
The purpose of this study is to demonstrate empirically whether there is an effect of Budget Goal Clarity, Organizational Commitment, and Environmental Uncertainty to Revenue Budget Accuracy and Expenditure Budget Accuracy in Bali Provincial Government SKPD. Method of sampling technique used on this study is Simple Random Sampling Method with total sample of 85 people. In this study, the secondary data is taken from SKPD Budget and Realization data of Bali Provincial Government in 2011, while the primary data is obtained from questionnaires. The analysis technique is Multiple Linear Regression Analysis. The study results indicate that the Budget Goal Clarity and Organizational Commitment has a positive effect to the Revenue and Expenditure Budget Accuracy, on the other hand the Environmental Uncertainty has a negative effect to the Revenue and Expenditure Budget Accuracy. Keywords: budget goal clarity, organizational commitment, environmental uncertainty, and the budget accuracy.